Apprenticeship as a model for the international architecture of TVET - Gonon, Philipp [Verfasser] (My University, 2011)
"This paper focuses on the nature and future of apprenticeships. It is important to have a clear notion about apprenticeship or rather of how the concept is used today. Apprenticeships are regarded as one promising way of a well organised TVET (Technical Vocational Education and Training). Generally, apprenticeships as a basic element of TVET should be well integrated into the education system. The topical move of reinventing apprenticeship in England, France and other countries around the world is part of a policy-driven agenda. In classical 'dual-system' countries like Germany, Austria and Switzerland apprenticeships have to adapt to a new context as well. The future of apprenticeship will be a hybrid form of work-based practice and school-oriented learning." (Autorenreferat, BIBB-Doku)
Keywords: Berufsbildungssystem; Reform; Berufsbildungstheorie